Răspuns :
2x=4√(x-1) +3 . x-1≥0
2x-3 =4√(x-1), ridicam la patrat ambii membri si obtinem:
4x^2-28x+25=0, se aplica formula de rezolvare.
Obs. Ce-i sub radical?
2x-3 =4√(x-1), ridicam la patrat ambii membri si obtinem:
4x^2-28x+25=0, se aplica formula de rezolvare.
Obs. Ce-i sub radical?
[tex]2x=4\sqrt{x-1}+3\\
2x-3=4\sqrt{x-1}|()^2\\
4x^2-12x+9=16(x-1)\\
4x^2-12x+9=16x-16\\
4x^2-28x+25=0\\
\Delta=784-4*4*25\\
\Delta=384=\ \textgreater \ \sqrt{\Delta}=8\sqrt6\\
x_1=\frac{28-8\sqrt6}{8}\\
x_1=\frac{4(7-2\sqrt6)}{8}\\
x_1=\frac{7-2\sqrt6}{2}[/tex]